Enhancing Arabic Speaking Skills: A Societal Approach at an Indonesian Islamic Boarding School University - Implementation Challenges and Remedies - Mahfuz Rizqi Mubarak; Audina, Noor Amalina; Muhammad, Bimaghfirlana (Journal of Arabic Language Learning and Teaching (JALLT), 2023)
The research explores the implementation of teaching speaking skills to first-semester Arabic language students at the University of Islamic Boarding School in Indonesia, using a social approach. It aims to comprehensively describe the process, covering objectives, the roles of lecturers and students, discussion themes, teaching methods, media, and evaluation. The study employs a descriptive qualitative method with data collected through observation, interviews, and documentation. Insights from the findings highlight the sociological perspective of learning objectives, emphasizing the lecturer's role in fostering social interactions through discussions. Both the lecturer and students' roles are examined in a societal context, underlining the lecturer's societal responsibilities and students' readiness for societal engagement. Discussion themes include social elements such as good behavior, Islamic education, and youth. The teaching method involves a conversational approach with cooperative learning strategies. Classroom media is limited to books and boards, while dormitories are equipped with LED TVs broadcasting Arabic-language religious speeches. Challenges faced by students are categorized into internal (lack of personal motivation) and external problems (shortage of classrooms and inadequate bathroom facilities). The study provides insights into the practical and sociological aspects of teaching speaking skills in an Islamic educational environment.